PENDAMPINGAN MASYARAKAT DESA SEHAT MELALUI PENYULUHAN KANKER STUNTING DAN PENYAKIT MENULAR SEKSUAL DI DESA PENGADANGAN - Yogiswara, I Gede Arya; Aenaya, Alsya Siti; Apriani, Rani; Rahman, Baiq Bintan Julia; Dewi, Sintianti; Hatimah, Husunul; Pratama, Andrian; Putri, Anastasya Diah Lestari; Wienagatha, Baiq Lovina; Al-Amirullah , Muhammad (Universitas Mataram, 2023)
Kuliah Kerja Nyata (KKN) is a form of community service activity carried out by tertiary institutions. This service activity was carried out by a group of students and lecturers from the University of Mataram with the theme Healthy Village. In the KKN activities carried out in Pengadangan Village, Pringgasela District, East Lombok Regency, the KKN team carried out various activities with the main target being the health problems of the Pengadangan Village community. The purpose of this KKN activity is to provide assistance and education to the Pengadangan Village community about the dangers of cancer and sexually transmitted diseases and help the community to minimize the stunting rate in Pengadangan Village. There are four methods of activities carried out, namely (1) Stunting counseling with posyandu cadres in Pengadangan Village, (2) Participating in Posyandu activities in each hamlet, (3) Holding a quiz competition between posyandu cadres with the theme of Stunting, (4) Counseling as well as free examinations of cancer and sexually transmitted diseases. The results of this activity are first, the community knows the causes and ways to prevent stunting. Second, posyandu cadres are helped in carrying out their activities. Third, increased knowledge among cadres about stunting. And finally, the community gained knowledge about cancer and sexually transmitted diseases ranging from indications, characteristics and how to prevent them and the community can also conduct free examinations to find out whether there is an indication of a disease or not. In addition, the KKN team was also involved in various other activities such as providing counseling and literacy on the importance of waste selection and processing, making RT signs, and holding a healthy walk as a form of our farewell event. The results of the above activities show that this KKN activity is able to provide assistance to the Pengadangan Village community in an effort to realize a Healthy Village.